2008
DOI: 10.1007/s10802-008-9262-4
|View full text |Cite
|
Sign up to set email alerts
|

Empathy and Social Perspective Taking in Children with Attention-Deficit/Hyperactivity Disorder

Abstract: This study explored empathy and social perspective taking in 8 to 12 year old children with and without Attention-Deficit/Hyperactivity Disorder (ADHD). The sample comprised 92 children, 50 with a diagnosis of ADHD and 42 typically developing comparison children. Although children with ADHD were rated by their parents as less empathic than children without ADHD, this difference was accounted for by co-occurring oppositional and conduct problems among children in the ADHD sample. Children with ADHD used lower l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
90
0
11

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(110 citation statements)
references
References 54 publications
9
90
0
11
Order By: Relevance
“…These combined findings are consistent with other studies showing that children with ADHD have poorer social perspectivetaking skills than non-diagnosed children (Marton, Wiener, Rogers, Moore, & Tannock, 2009). …”
Section: Children With Adhd In Interaction With Their Friendssupporting
confidence: 93%
See 1 more Smart Citation
“…These combined findings are consistent with other studies showing that children with ADHD have poorer social perspectivetaking skills than non-diagnosed children (Marton, Wiener, Rogers, Moore, & Tannock, 2009). …”
Section: Children With Adhd In Interaction With Their Friendssupporting
confidence: 93%
“…Given the central importance of this principle in theories about friendship, this problem may be central to all of our other findings. Controlling behaviours may also be the consequence of poor perspective-taking skills (Marton et al, 2009), manifested by a failure to effectively integrate the friend's perspectives and occasionally give up some of one's own feelings.…”
Section: Children With Adhd In Interaction With Their Friendsmentioning
confidence: 99%
“…Moreover, a recent study with 172 children with ADHD found that poorer teacher-reported social self-control was associated with children's greater externalizing behavior, which was then linked to receiving fewer "like most" nominations from peers [38]. Other research suggests that social cognitive deficits such as poor perspective taking skills, reduced empathy, theory of mind problems, overestimation of one's own social competence, social information processing biases, and sensation seeking goals may also contribute to the peer problems of children with ADHD [41][42][43][44][45]. These findings are essential to understanding how problem behaviors and social skills deficits in children with ADHD lead to peer rejection.…”
Section: Historical Conceptualizations Of Peer Problems In Adhdmentioning
confidence: 99%
“…Attention deficits might also partially account for the lack of empathy (a construct closely linked to mentalizing) often observed in subjects suffering from ADHD; difficulties to focus attention while interacting with someone could certainly lead to difficulties in understanding their feelings and the ability for cognitive and emotional perspective-taking (Braaten and Rosen, 2000;Deschamps et al, 2015;King et al, 2009;Marton et al, 2009;Matthys et al, 1999;Roy et al, 2013). Taking these findings into account, one might hypothesize that the lack of empathy and the poor social cognition found in ADHD subjects is partly the result of poor RF.…”
Section: Introductionmentioning
confidence: 99%